CFD investigation on the hydrodynamic loads and motions when ship maneuvers in regular and irregular waves. (15th December 2022) - Ma, Chengqian; Hino, Takanori; Ma, Ning; Takagi, Youhei
Abstract: To explore and predict the ship maneuverability in the regular and irregular waves, the zigzag tests, the turning tests, and the course-keeping tests for the model-scale S175 containership under various wave conditions are simulated. The simulations are performed using a structured overset Unsteady Reynolds Averaged Navier-Stokes (URANS) solver with a moving grid. A body force method is adopted to predict the propeller forces. The simulation results are validated by the free-running experiments with satisfactory accuracy, which indicates that the present simulation strategy is effective and reliable. The hydrodynamic loads on the hull and the rudder together with the ship motion characteristics during the maneuvers in waves are obtained. It is concluded that the ship motions and hydrodynamic loads increase with the increase of the wavelength when the wave height is kept constant. The variation trends and magnitudes for low-frequency components of the self-propulsion factors in waves are similar to those in the calm water condition except obvious high-frequency fluctuations due to the wave effect. For the zigzag tests under the long-crested and short-crested irregular waves, the time histories of the yaw and rudder angle are similar. For the turning tests, the amplitude of roll motion in waves is much larger compared with that of the zigzag tests under the same wave condition, and the drift of the trajectory due to the wave is obvious. The current course keeping simulation can be an alternative tool to predict course keeping maneuvers in waves. Furthermore, flow visualizations are presented for providing a better understanding of the wave effect on free-running ship maneuvers. Highlights: The simulations on free-running tests in waves are performed using a structured Reynolds Averaged Navier-Stokes solver. The hydrodynamic loads, the self-propulsion factors, and the ship motions during the maneuvers are obtained. The zigzag maneuver motions under the long-crested and short-crested irregular wave conditions are compared. The tuning maneuver with a moving rudder and the course-keeping maneuver with a PID controller in waves are simulated. The typical flow fields during the maneuvers are presented to explore the evolution of the flow field.